Quantitative Assessment of Heavy Metals and Microbial Contaminants in some Lipsticks in Western Part of Nigeria - Kasim , L. S.; Akintona , M. O.; Daodu , J. O.; Olufolabo , K. O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Lipsticks are part of cosmetics many women use to improve on their outlook but may constitute a health hazard if varying concentration of heavy metals and pathogenic microorganisms are associated with their use. This study was carried out to investigate the concentration of heavy metals and bacterial load of associated microorganisms present in some lipstick samples. Ten lipstick samples from five different brands were purchased from Ijebu-Ode, Ogun State, Nigeria. Each sample was prepared for analysis using 12.5 mls of nitric acid, 1.00 ml of sulphuric acid (H2SO4) and 2 ml of perchloric acid (HClO4) and digested electronically .The heavy metals analysis was carried out by Flame atomic absorption spectrophotometer. The microbial loads in each lipstick samples were determined using standard procedure. The results showed that Cobalt, Lead, Nickel, Copper and Cadmium were present in all the lipstick samples with concentrations of Cobalt ranges between 29.3 ppm to 10.8 ppm while that of Lead ranges between 56.4 ppm to 11.5 ppm and Nickel ranges between 57.7 ppm to 12.8 ppm only Copper and Cadmium being within WHO permissible limits. The samples were contaminated with Staphylococcus aureus and Escherichia coli and the total aerobic bacteria counts for all samples were similar and were above WHO permissible limits. This study revealed that the use of some cosmetic product could expose the users to low concentration of toxic heavy metals and pathogenic microorganisms which constitute potential health risk.